1998
DOI: 10.1002/(sici)1097-0274(199812)34:6<568::aid-ajim4>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Occupational dermatitis causing days away from work in U.S. private industry, 1993

Abstract: Background Occupational skin disease is an important cause of disability in the workplace. The aim of this report is to estimate the incidence of occupational dermatitis cases that causes days away from work and to characterize the cases. Methods The Annual Survey of Occupational Injuries and Illnesses from the Bureau of Labor Statistics collects employer reports on work‐related dermatitis. Descriptive data are collected on a sample of the cases that result in days away from work. Estimates of the number of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 3 publications
2
52
0
3
Order By: Relevance
“…The BLS conducts annual surveys of employers selected to represent all private industries in the US. The survey excludes approximately 23% of employed persons, including the self-employed, farms with fewer than 11 employees, private households, and government agencies [4]. It depends on compliance and reporting by the employer and employee, and the recognition and diagnosis of an occupational injury or illness.…”
Section: Public Health Importancementioning
confidence: 99%
See 3 more Smart Citations
“…The BLS conducts annual surveys of employers selected to represent all private industries in the US. The survey excludes approximately 23% of employed persons, including the self-employed, farms with fewer than 11 employees, private households, and government agencies [4]. It depends on compliance and reporting by the employer and employee, and the recognition and diagnosis of an occupational injury or illness.…”
Section: Public Health Importancementioning
confidence: 99%
“…A more thorough review, which looked specifically at cases with days away from work, used 1993 BLS data [4]. This review showed that of 60,200 cases of OSDs (76 per 100,000 workers), 12,613 (21%;16 per 100,000 workers) resulted in days away from work.…”
Section: Us National Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Chemical exposure can lead to contact dermatitis, the most common occupational skin disorder; responsible for up to 30% of all cases of occupational disease in industrialized nations. Epidemiologic data suggest that contact dermatitis accounts for ≈95% of all cases of occupational skin disease, imposing considerable social and economic implications (Burnett et al, 1998;Clark and Zirwas, 2009). Time off work, loss of workplace productivity, reduced quality-of-life, and medical and worker compensation costs are several factors accounting for the loss of billions of dollars.…”
Section: Introductionmentioning
confidence: 99%